Manusia Menurut Aliran Paguyuban Sumarah dan Pangestu Ditinjau dari Ajaran Islam - Herman, Nurwinda; Lubis, Dahlia; Ekowati, Endang (YASIN, 2023)
The aim of this research in general is to obtain a bachelor's degree (S1) in the Study of Religions study program and as additional reference material for future research. This type of research is library research, namely research carried out by collecting data and information in various ways such as reviewing several books, articles, magazines and so on. This research also uses a phenomenological approach. The phenomenological approach is the study of a person's life experiences or methods for how individuals subjectively perceive experiences and provide meaning to these phenomena. And this research also uses a comparative method, which means this research compares the situation of one or more variables. The results of this research, according to Paguyuban Sumarah and Pangestu, created humans based on four elements: fire, water, earth and air. However, in contrast to Islam, humans are created from the essence of the earth which is formed as well as possible and then the spirit is breathed into them.